PERAN KOMPOSISI DAN AKTVITAS KOMITE AUDIT DALAM MENINGKATKAN KINERJA KEUANGAN DENGAN UKURURAN PERUSAHAAN MENJADI VARIABEL KONTROL - RARA SILKFAN; R.MULTI KONVOKESEN ADIMAN; ASIH PUJI LESTYANINGRUM; MAHARANI AZWIR (JURNAL AKUNTANSI DAN KEUANGAN, 2025)
This study aims to analyze the role of audit committee composition and audit committee activity in improving corporate financial performance, with firm size used as a control variable. The effectiveness of the audit committee is an important issue in corporate governance, particularly regarding the quality of oversight in the financial reporting process. This study uses a quantitative approach with panel data consisting of 82 company observations during 2022-2024. The independent variables include audit committee size and audit committee meeting frequency, while financial performance is measured using Return on Assets (ROA). Firm size is incorporated as a control variable to examine the consistency of the audit committee’s influence on performance. The results indicate that audit committee size has a significant positive effect on ROA, suggesting that a larger number of audit committee members enhances the effectiveness of oversight. Audit committee meeting frequency also shows a significant positive effect, indicating that more intensive meeting activities are associated with improved financial performance. Conversely, firm size has a significant negative effect on ROA, implying that larger firms do not necessarily achieve higher profitability. These findings highlight the importance of effective audit committee oversight in driving corporate performance